Healing to all their flesh : Jewish and Christian perspectives on spirituality, theology, and health - Levin, Jeffrey S.; Meador, Keith G. (Templeton Press, 2012)
Healing to All Their Flesh asks us to step back and carefully rethink the relationship between religion and health. It does so by examining overlooked issues of theology and meaning that lie at the foundation of religion's supposed beneficial function. Is a religion-health relationship consistent with understandings of faith within respective traditions? What does this actually imply? What does it not imply? How have these ideas been distorted? Why does this matter-for medicine and healthcare and also for the practice of faith? Is the ultimate relation between spirit and flesh, as.